2021
DOI: 10.3389/fresc.2021.726210
|View full text |Cite
|
Sign up to set email alerts
|

Person-Centered Healthcare Practice in a Pandemic Context: An Exploration of People's Experience of Seeking Healthcare Support

Abstract: Background: The recent COVID-19 pandemic increased pressure upon healthcare resources resulting in compromised health services. Enforced national lockdown led to people being unable to access essential services in addition to limiting contact with social support networks. The novel coronavirus, and subsequent condition known as long covid were not well-understood and clinicians were not supported by existing guidelines or pathways. Our study explored people's experiences of healthcare during this period with a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
16
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(17 citation statements)
references
References 25 publications
0
16
1
Order By: Relevance
“…Similarly, pharmacists used innovative ways to engage with patients during mandatory post-vaccination wait. While many of the findings, such as a lack of time and workload pressures, are echoed in the literature as barriers to the implementation of opportunistic health behaviour change interventions pre-pandemic (Keyworth et al, 2019(Keyworth et al, , 2020bParchment et al, 2021), the current results add to the evidence that the health service overall, in its response to the pandemic, became less holistic and patient-centred (Curnow et al, 2021). Thus, it is paramount that the NHS is equipped with the resources and tools to ensure that the prevention and management of long-term health conditions is a focus of routine healthcare consultations in the months to come.…”
Section: Comparison With Existing Literaturementioning
confidence: 74%
“…Similarly, pharmacists used innovative ways to engage with patients during mandatory post-vaccination wait. While many of the findings, such as a lack of time and workload pressures, are echoed in the literature as barriers to the implementation of opportunistic health behaviour change interventions pre-pandemic (Keyworth et al, 2019(Keyworth et al, , 2020bParchment et al, 2021), the current results add to the evidence that the health service overall, in its response to the pandemic, became less holistic and patient-centred (Curnow et al, 2021). Thus, it is paramount that the NHS is equipped with the resources and tools to ensure that the prevention and management of long-term health conditions is a focus of routine healthcare consultations in the months to come.…”
Section: Comparison With Existing Literaturementioning
confidence: 74%
“…The saturation of the health systems led to a decrease in the quality of services [ 19 , 20 ] and person-centered care [ 21 ]. Patients encountered barriers to accessing health services [ 21 , 22 ], communication difficulties with healthcare providers [ 23 ], and lack of social support, among other difficulties [ 22 , 24 ].…”
Section: Introductionmentioning
confidence: 99%
“…The saturation of the health systems led to a decrease in the quality of services [ 19 , 20 ] and person-centered care [ 21 ]. Patients encountered barriers to accessing health services [ 21 , 22 ], communication difficulties with healthcare providers [ 23 ], and lack of social support, among other difficulties [ 22 , 24 ]. COVID-19 patients have had pronounced healthcare needs, with approximately half of them needing physical, cognitive, and psychological follow-up care post-acute symptoms’ resolution [ 25 , 26 , 27 ].…”
Section: Introductionmentioning
confidence: 99%
“…First studies have shown that many people with long COVID perceive their medical care as inadequate [22], [23]. They describe a lack of acceptance of their symptoms by health professionals, which leads to uncertainty and the feeling of being left alone [22], [24], [25]. This represents an obstacle to needs-based medical care.…”
mentioning
confidence: 99%